Reviewing the knowledge on the genus Patella in the Mediterranean Sea: testing the effect of protection on the mean abundance and size of Patella ferruginea - Cascales-Soler, Ana; Ramos-Espla, Alfonso Angel; Forcada, Aitor (Frontiers in Marine Science, 2023)
Increasing human pressure has strongly impacted the littoral environment, altering the habitats and population parameters of some species. The Mediterranean Sea is one of the regions that have been highly affected by these events. In response to these events, marine protected areas (MPAs) have emerged as one of the main conservation tools for marine habitats and species. In this regard, harvesting of limpets (Patella spp.) is a good example of the impact of human activity on the coast. Limpets are mollusks that are collected as food or fishing bait, and their exploitation causes an immediate decrease in the density and size structure of individuals. In the Mediterranean Sea, the genus Patella is represented by five species: Patella rustica, P. caerulea, P. ulyssiponensis, P. ferruginea, and P. depressa. To verify the effectiveness of the MPAs, a deep review of 75 studies on Patella spp. in the Mediterranean Sea was conducted to analyze the spatial and temporal distribution of studies. Data extracted from these articles were used to assess the effect of protection on the density and size of P. ferruginea. Regarding spatial distribution, the studies reviewed were performed at 67 sites in 13 countries, of which 23 were in MPAs and 44 in non-protected or control areas. The findings of this study show that P. ferruginea is the species most studied, because it is one of the most threatened marine invertebrates in the Mediterranean Sea. This explains the temporal distribution of the studies, which coincides with the establishment of the conservation status and the concern about the population status of P. ferruginea. Analysis of the effect of protection on the density and mean size of P. ferruginea individuals revealed no significant difference in mean density between the control sites and MPAs. However, mean size between individuals was significantly higher in MPAs than control sites. This pattern may be related to intra- and interspecific competition between individuals.